Genocide and resistance Nr. 57(1) - Tumavičius, Andrius; Zizas, Rimantas; Vyšniauskas, Arūnas; Klumbys, Valdemaras; Banionis, Juozas; Pletzing, Christian; Kalniņš, Pēteris (Genocidas ir rezistencija, 2025)
Full Issue